Development of the School Teachers Job Stressor Scale (STJSS) - Keiko Naono‐Nagatomo; Hiroshi Abe; Hironori Yada; Kenichi Higashizako; Michihiko Nakano; Ryuichiro Takeda; Yasushi Ishida (Wiley, 2019)
Abstract Aim Japanese teachers are not only responsible for students but also for tasks outside the classroom, including engagement with parents and the community, and maintaining safety. They work longer hours and have lower self‐efficacy than teachers in other countries. Thus, we aimed to develop an assessment scale for job stress in teachers and to evaluate its psychometric properties. Methods We developed the "School Teachers Job Stressor Scale (STJSS) Draft" comprising 45 items, based on previous anonymous self‐report questionnaires collected from 98 teachers in four elementary and middle schools in Miyazaki City, Japan. Subsequently, the scale draft and the previously validated Brief Job Stress Questionnaire (23‐item abridged version) were distributed to 2276 teachers from 73 elementary and middle schools in Miyazaki City. Finally, we analyzed data from 1300 participants. After excluding inappropriate data based on ceiling and floor effect analysis, we carried out a good‐poor, item‐total correlation, and exploratory factor analyses. We then verified construct validity, criterion‐related validity, and reliability using correlation analysis, confirmatory factor analysis, and Cronbach's alpha, respectively. Results After item‐total correlation analysis, five items were excluded. Exploratory factor analysis extracted five factors: "Time spent outside of work," "Self‐assessment of one's ability as a teacher," "Relationship with other teachers," "Social interactions outside of teaching," and "Duties outside of teaching." The final version of the STJSS comprised 23 items and five factors. Conclusion The 23‐item STJSS developed to measure specific stressors in Japanese teachers to improve their mental health care could provide an accurate assessment tool with adequate reliability and validity.